Pengaruh Kompensasi Dan Disiplin Terhadap Kinerja Karyawan Di Dinas Kebudayaan Bantul D.I.Yogyakarta - Romadhoni, Romadhoni; Fahlefi, Wilis (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2024)
The purpose of this research is to determine the effect of compensation and discipline on employee performance at the Bantul Culture Service, Yogyakarta Special Region. The population in this study was all employees at the Culture Service, Bantul, D.I Yogyakarta as many as 40 people, while the sample used a saturated sample where the population was used as a sample. Data collection was carried out by distributing questionnaires to respondents. Collection technique using SPSS.17. Data analysis uses multiple regression. Based on the research results, it is stated that compensation and discipline have a significant and influential effect on employee performance at the Bantul D.I. Culture Service. Yogyakarta.